Metabolic Syndrome and Obesity Update - Cunningham, Muriel (MD Conference Express, 2006)
Is the metabolic syndrome a useful tool for clinicians or is it clinically irrelevant? This article discusses the debate the merits of this collection of symptoms, childhood obesity, new paradigms of obesity and diabetes in youth, the use of pramlintide in the treatment of obesity, and stress eating.